CYBERPHYSICAL SYSTEMS FOR AUTOMATION OF ENTERPRISE PREMISES - MELNYK, VIKTORIIA; KRYVAK, DENYS; VOZNYI, KYRYLO; HURALNYK, OLEKSANDR; DROZD, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A building automation system, which is a complex distributed control system, is widely used in commercial, residential and industrial buildings to monitor and control mechanical or electrical equipment. Industrial and technological progress in the part of control components are becoming more and more interconnected. The potential advantages and, integration generate and encourage new attacks, which significantly increases the risks to the security and protection of their management system. Not all building automation systems are designed to have a robust security architecture and rely mostly on physical isolation and "security through obscurity" in this regard. These methods are not suitable for "smart building" technologies. In this regard, the security and protection of the current building automation system needs to be reassessed and the development of a comprehensive solution that will ensure integrity, reliability and confidentiality at both the system and network levels. Therefore, the goal of the work was the development at the system level of providing a reliable computing basis for devices and controllers. Using desirable security features such as robust modular design, small privilege code, and formal verifiability of the microkernel architecture, enhanced security of operating systems with built-in mandatory access control and a proxy-based communication framework for building automation controllers needs to be described, i.e. ensuring functioning of cyber-physical systems. This solution provides policy-compliant communication and isolation between critical and non-critical applications in a potentially hostile cyber environment. A method of processing messages and configuring the microkernel has been developed. Its implementation is based on a form of endpoint capability allocation that occurs in the root initialized user process. The proposed method of creating a safe cyber-physical system for the automation of enterprise premises is presented. It is based on microkernel architecture. Conducted research on the proposed microkernel-based cyber-physical system showed the need to improve operating systems and their importance in the context of such tasks. The direction of further research is to improve the functions of microkernel-based operating systems for their use in cyber-physical building automation systems in the context of security.